2015
DOI: 10.1155/2015/603148
|View full text |Cite
|
Sign up to set email alerts
|

Surface Patterning of PEDOT:PSS by Photolithography for Organic Electronic Devices

Abstract: Along with the development of organic electronics, conductive polymer of PEDOT:PSS has been attracting more and more attention because they possess various novel electrical, optical, and mechanical properties, which render them useful in modern organic optoelectronic devices. Due to its organic nature, it is lightweight and can be fabricated into flexible devices. For better device processing and integrating, it is essential to tune their surface morphologies, and photolithography is the best choice at present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…In conclusion, photolithography is in principle a planar technique, which is suitable for the fabrication of 2D micro‐/nanostructures at the surface of the resist . Advantages of photolithography are high throughput capabilities, straightforward scaling to large area substrates, ultrahigh resolution, etc . However, conventional photolithography involves the use of custom‐made masks and other optical component, which increases the cost and time from design to prototype .…”
Section: Fabrication Of Micro‐/nanostructurementioning
confidence: 99%
“…In conclusion, photolithography is in principle a planar technique, which is suitable for the fabrication of 2D micro‐/nanostructures at the surface of the resist . Advantages of photolithography are high throughput capabilities, straightforward scaling to large area substrates, ultrahigh resolution, etc . However, conventional photolithography involves the use of custom‐made masks and other optical component, which increases the cost and time from design to prototype .…”
Section: Fabrication Of Micro‐/nanostructurementioning
confidence: 99%
“…From a manufacturing perspective, it is essential to establish the least complicated process flow to form micropatterns of CPs without any potential modification of the desired conductivity and surface morphology. Printing (ink-jet printing 27 and roll-to-roll printing 28 ), lithography (photolithography 29 , nanoimprint lithography 30 , UV and e-beam lithography 31 ), and direct etching (laser ablation 32 and plasma etching 33 ) are presently the mainstream micropatterning techniques for CPs. Among them, photolithography has attracted the most attention because of its low cost, high resolution, compatibility with the established manufacturing process, and large surface area patternability 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, we also tried to investigate the effects and results of doing wet processing on a PEDOT:PSS film. Ouyang et al (2014) [36] proposed a process for PEDOT:PSS This process may be interesting to use, especially in a commercial process, because of its ease in integration into todays semiconductor processing; especially the use of photo-lithography as a patterning step, since it provides a straightforward path for large integration scaling where really fine features are required (eg. a pixel display).…”
Section: Lift-offmentioning
confidence: 99%
“…However, Lang et. al (2007) [37] and Ouyang et al (2014) [36] have demonstrated that through careful selection of materials for deposition and processing, the PEDOT:PSS films can be minimally damaged during liftoff process.…”
Section: Lift-offmentioning
confidence: 99%